Additional lines in quantum wells excitonic spectra connected with QW asymmetry caused by technology - Ryabchenko, S.M.; Kirichenko, F.V.; Semenov, Yu.G.; Abramishvili, V.G.; Komarov, A.V. (Condensed Matter Physics, 1999)
The calculations of intensity ratio of both the main and additional lines, the energy differences between which are fulﬁlled for quantum well (QW) with asymmetrical potential proﬁle, are presented here. It is grounded on the basis of this calculation that additional line in exciton spectrum of QW can be explained by transitions between the conﬁned states of valence and conductivity electrons with different parity, which ceases to be forbidden in the presence of asymmetry of QW potential proﬁle caused by technology of growth. It is shown that e1-hh2 additional exciton line is more intensive in most of the actual cases. In particular, it is shown that the additional exciton line, which was observed in the laser ablation grown structures with QW, may be explained as e1-hh2 transition. The calculations show the substantial sensitivity of the results not only to the parameter of widening of the interface, but to the detailed type of the interface proﬁle function. It is concluded that the laser ablation method of heterostructure growth leads to a larger asymmetry of QW potential proﬁle caused by technology than MBE potential proﬁle.